Pogledi na podomačevanje tujih zemljepisnih imen - Kladnik, Drago (Georitem, 2007)
A geographical name or toponym is a proper name that by definition firmly and unquestionably identifies and individualizes a specific geographical phenomenon or topographical object. All geographical names in the world and in every language are divided into endonyms and exonyms.An "endonym" is the name of a geographical feature in one of the languages occurring in the area where the feature is situated. An "exonym" is a name used in a specific language for a geographical feature situated outside the area where that language has official status and differs in form from the name used in the official language or languages of the area where the geographical feature is situated.The use of geographical names can be politically sensitive, and for this reason this issue has long been the subject of international discussion. To strengthen the role of international professional associations in this field, in 1959 the United Nations established the United Nations Group of Experts on Geographical Names (UNGEGN), which directs international activities in the field of geographical names.